Conservation management plans: An examination of obstacles to, and opportunities for, producing an effective management tool. Issue 4 (22nd October 2019) - Worthing, Derek; Organ, Samantha
Abstract : Purpose: The purpose of this paper is to identify factors that contribute to the development of an effective conservation management plan (CMP). Design/methodology/approach: The approach was based on a literature review from which key issues and concerns were identified. This was followed by in-depth interviews with a number of creators and users of CMPs. Findings: CMPs have developed as an identifiable process with the key stages having a logic and synergy with each other. The research found that undue emphasis was placed on some stages at the expense of others which lead to ineffective management tools often being produced. The reasons for this are related to the interests and background of the creators and a lack of interaction with organisational culture and processes – and importantly a failure to engage with frontline staff. In addition, there were also resource and skill constraints within the client organisation. Research limitations/implications: Interviews were conducted with six creators (consultants) and seven users. These were mostly from national heritage organisations and specialist heritage consultants. A wider range of user organisations and consultants could be identified for follow-up research. Also those who actually deliver CMPs "on the ground" and day to day could form an important part of the development of this research. Practical implications: CMPs should be practical working management tools which have to be used by the heritage organisation in order to be effective. This research will hopefully help practitioners focus on what needs to be done in order to produce an effective plan. Social implications: The conservation of built heritage is essentially concerned with the protection of a social good. CMPs have the potential to provide effective protection of that which is seen as valuable and significant to individuals, groups and society at large. Originality/value: The management of heritage is an area that is generally under-researched. This work will hopefully be engaged with by academics and practitioners in order to help establish and promote a wider interest in the field.